Changing practice to improve pain control for renal patients. Issue 999 (24th February 2009) - Salisbury, E M; Game, D S; Al-Shakarchi, I; Chan, M; Fishman, L; Tookman, L; Brown, E A
Abstract : Pain is a common symptom described by patients with end-stage kidney disease (ESKD) but remains ineffectively managed. The aim of this audit was to determine what proportion of these patients report pain, then introduce the use of an analgesic ladder adapted specifically for ESKD, and finally re-evaluate the prevalence of pain symptoms, looking for an improvement. A cohort of inpatients on the renal wards of a West London teaching hospital was studied. The number of patients reporting pain and the severity of their pain on a scale of 1–10 were recorded. A considerable number of patients were barred from participating because of a language barrier. Interpreters were introduced, and the phase was repeated. The World Health Organization (WHO) three-step analgesic ladder was adapted for patients with ESKD and introduced to medical staff on the renal wards. The number of patients reporting pain and the severity of their pain were re-recorded. There was a significant reduction in the number of patients reporting pain and the severity of their pain. Pain control in patients with ESKD is improved through the use of an adapted version of the WHO analgesic ladder. Strategies must be in place for effective communication with foreign patients.